2015
DOI: 10.1007/s10681-015-1506-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterotic responses among crosses of IITA and CIMMYT early white maize inbred lines under multiple stress environments

Abstract: Two major constraints militating against the achievement of food security in West Africa (WA) are recurrent drought and poor soil fertility. Seventeen early maturing maize inbreds from IITA and CIMMYT were used as parents to produce 136 diallel crosses which were evaluated along with four checks in contrasting environments at four locations for 2 year in Nigeria. The objectives of the study were to (i) examine the combining ability of the lines under drought, low soil nitrogen (low N), optimal and across envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 42 publications
0
40
4
1
Order By: Relevance
“…For details on the observations made on traits and the appropriate scoring scales used in this research, refer to Badu‐Apraku et al. ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For details on the observations made on traits and the appropriate scoring scales used in this research, refer to Badu‐Apraku et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…The statistical model employed for the combined analysis in the present study has been previously described by Badu‐Apraku et al. (). Broad‐sense heritability (H 2 ) of the traits was estimated as the proportion of the phenotypic variance contributed by the genetic variance based on the hybrid means, following the method of Hallauer, Carena, and Filho ().…”
Section: Methodsmentioning
confidence: 99%
“…The authors found the HSGCA method to be superior to the SCA effect of grain yield method. In a similar study involving IITA and CIMMYT early-maturing white maize inbreds evaluated under multiple stress environments, the HSGCA method classified the lines into three groups and was the most efficient because it had the highest breeding efficiency in the test environments followed by the HGCAMT, SNP marker-based GD and the SCA effects of grain yield methods (Badu-Apraku et al, 2015b). Similarly, Akinwale et al (2014) identified HSGCA as the most efficient method in classifying early-maturing tropical maize inbreds under Strigainfested and Striga-free environments.…”
Section: Comparison Of the Efficiency Of The Heterotic Grouping Methodsmentioning
confidence: 99%
“…SCA variance was found to be non-significant, suggesting the preponderance of additive gene action for FSR resistance at this location. It suggests that early generation testing would be effective and selection of hybrids could be solely based on the prediction of GCA effects (Badu-Apraku et al, 2015). The relative importance of GCA and SCA effects was estimated by the ratio of GCA effects to the total genetic effect (Baker, 1978).…”
Section: Gene Action and Combining Abilities For Fsrmentioning
confidence: 99%